“The only ones I could rely on”: An Exploration of the International Athlete Experience at NCAA Division I Institutions - Chris Corr; Nicole Sellars; Christopher Atwater; Charles Macaulay; Karina Jolly; Sarah Stokowski; Marek Taškár (Journal of Applied Sports Management, 2025)
International athletes constitute a significant demographic within NCAA Division I athletics, offering diverse cultural perspectives and often enhancing team performance. Despite the documented importance of social support structures in facilitating their socio-cultural adaptation, the role of institutional and organizational support remains underexplored. This study aims to bridge this gap by examining the experiential satisfaction of international athletes competing in NCAA Division I sports, with a particular focus on their perceptions of institutional and organizational support. Utilizing a qualitative approach, semi-structured interviews were conducted with 33 international athletes across multiple NCAA Division I institutions. The findings reveal varying degrees of dissatisfaction, particularly with institutional support, which appears to influence the athletes' overall experiences and their willingness to recommend NCAA participation to prospective international athletes. These insights suggest a need for NCAA institutions to reassess their support structures to better serve their international athlete populations and sustain their competitive advantage on a global scale.
Keywords: athletic transition; recruiting; athlete satisfaction